Antitrust Regulation in the Era of Digital Market - A new perspective considering covert channel and artificial intelligence with technical demonstration - Bayer, Siming; Sun, Yipeng; Maier, Andreas; Hoffmann, Jochen (TilTing Perspectives 2024, 2024)
In digital commerce, antitrust legislation faces new challenges from AI-driven market mechanism automation, such as dynamic pricing algorithms. This development extends the role of market actors beyond humans, enhancing efficiency but also raising concerns about competition and market dynamics. A primary focus in Antitrust and AI research, as discussed by, is the significant impact of algorithmic integration in marketplaces, marking a transformative factor in this field. Contrasting with the recognized impact of AI, the role of covert channels in digital-era antitrust regulation has received less attention. These channels, which are unconventional methods for transferring information, present risks in online marketplaces, notably in illegal price-fixing. They are categorized into resource and time-based types and signify a shift in how secret communications might enable anti-competitive behaviors, which historically relied on direct interactions between market players. The integration of AI in pricing, which complicates the detection of illegal practices like price fixing and enables AI-driven collusion, necessitates a reevaluation of antitrust regulations. This combination of AI, covert channels, and conventional practices highlights the need for updated legal frameworks. Our research utilized structured experiments to simulate collusive pricing strategies with AI and covert channels, using real-world e-commerce data. This method offers insights into the mechanisms of price collusion in digital markets.<br
Keywords: AI; Antitrust; Covert Channel Collusion